Considerations in surgical versus non-surgical management of HPV positive oropharyngeal cancer. Issue 1 (December 2016) - Fundakowski, Christopher; Lango, Miriam
Abstract Given the marked difference in clinical presentation and treatment response based on human papilloma virus (HPV) status, HPV-associated oropharyngeal squamous cell carcinoma is now viewed as a distinct biologic and clinical entity. HPV-associated oropharyngeal squamous cell carcinoma has increased by nearly 7.5 % per year, from approximately 16 % in the early 1980′s to nearly 70 % today, and is believed will continue to increase dramatically in the coming years. Currently, a myriad of treatment options exist for these patients as many active clinical trials are underway which aim to identify the most appropriate interventions for this unique group of patients. This review aims to provide considerations between surgical and non-surgical management for HPV-associated oropharyngeal squamous cell carcinoma.